Manajemen Nyeri Pada Lansia Dengan Osteoartritis Lutut Dengan Pemberian Terapi Akupresur di Desa Bangun Rejo Kecamatan Tanjung Morawa Tahun 2023 - Adelina Sembiring; Lisbet Gurning; Beltiana Beltiana; Gloria Devi Simbolon (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Osteoarthritis is the most common type of arthritis that affects the knee. Osteoarthritis is a degenerative process in which joint cartilage is gradually eroded. This disease often attacks middle-aged and elderly people. Osteoarthritis can be caused by excessive stress on the joints such as repeated injuries or being overweight. The aim of this activity is to provide acupressure therapy to reduce the level of pain experienced by elderly people with knee osteoarthritis. The target of this activity is elderly people who experience knee osteoarthritis in Bangun Rejo Village, Tanjung Morawa District with a total of 16 people. This activity is carried out by providing acupressure therapy. The results of the activity showed a decrease in pain levels in elderly people with knee osteoarthritis in Bangu Rejo village, Tanjung Morawa district. It is hoped that the elderly can manage pain with knee osteoarthritis by providing acupressure therapy